Kontribusi sikap perawat terhadap upaya pencegahan risiko jatuh di ruang rawat inap bedah RSUD dr. Zainoel Abidin Banda Aceh - Vera Ariska; Erlia Rosita (Nur Science Institute, 2024)
Patient safety is a top priority for maintaining the quality of hospital services, and one way to achieve this is by preventing patient falls, which can cause serious injuries. This study aims to determine the relationship between nurses' attitudes and the implementation of fall risk prevention in the Inpatient Surgical Ward of Dr. Zainoel Abidin Regional Hospital, Banda Aceh. This study used a correlative analytical design with a cross-sectional approach. The study sample consisted of nurses in the inpatient surgical ward, selected using stratified random sampling. Data were collected through questionnaires on respondents' characteristics and nurses' attitudes, and an observation sheet on the implementation of fall risk prevention. The results showed that nurses' attitudes were related to the implementation of fall risk prevention. A positive attitude among nurses plays an important role in supporting patient safety efforts by implementing effective preventive measures. Hospitals are advised to improve education and strengthen the culture of patient safety to optimize the quality of health services.